Yale Divinity School and the Disciples of Christ, 1872-1989 - Becker, Edwin L. (Disciples of Christ Historical Society, 1990)
For many years, Disciples of Christ students well out-numbered Congregationalists and Methodists at Yale Divinity School, and this led to a "mainstreaming" of Disciples within the broader Protestant world. Yale Divinity School and the Disciples of Christ documents this transition, noting all graduates of Yale with ties to Disciples between 1872 and 1989. This important book shows the lasting impact of Yale on higher education, pastorates, denominational offices, foreign missions, and theological scholarship. The mainstreaming of Disciples of Christ in the 1920s was greatly shaped as its ministers pursued higher education. Becker's study shows the important place of Yale Divinity School in Disciples history. Though at one time, the University of Chicago trained more ministers than Yale, by the 1970s more than 600 clergy serving in Disciples of Christ had received their training from the Yale Divinity School